Evaluation of Product Yield and Fatty Acid Composition of Three Flax (Linum usititassimum L.) Varieties Depending on Different Sowing Dates - Yalinkilic, Nazli Aybar; Bayram, Silan Cicek; Basbag, Sema (Mdpi, 2025)
The flax (Linum usititassimum L.) plant can grow in various agroecological environments. However, there are some factors that affect the production and quality of flax. Sowing date is one of the important factors determining crop productivity. In this study, four different sowing dates (20-22 March, 1-3 April, 15-18 April and 30 April, respectively) were applied to determine the appropriate sowing date in terms of yield and oil quality in three flax varieties (Sar & imath; Dane, Kara K & imath;z, Beyaz Gelin). The study results showed that by delaying sowing, the seed filling period of the plant was exposed to high temperatures, and this caused decreases in seed yield. In other words, the most positive results in terms of agronomic characteristics were obtained from the first sowing date. In this respect, the highest oil yield of 760 kg ha-1 and the highest oil content of 34% were obtained from the Sar & imath; Dane variety. Similarly, flaxseed showed high values in terms of alphalinolenic acid (54.25%), palmitic acid (6.36%), stearic acid (7%), oleic acid (22.54%) and linoleic acid (14%) at the first and second planting times, while these rates decreased relatively as the planting time was delayed. According to the results of the two-year study, it was determined that the ecological conditions of the region were suitable for flax cultivation. However, it is clear that delaying the sowing date causes significant decreases in both the agronomic traits of flax and the oil quality for industrial purposes. In this respect, considering the ecology of the region, sowing flax in the last week of March or the first week of April is suitable for optimum yield and oil quality.
Keywords: yield components; ecological factors; alphalinolenic acid (ALA); flaxseed; biplot analysis; correlation analysis